Pie diabético - Echeverría G., Valentina; Sotomayor L., Camila; Norambuena G., Mackarenna; Vidal V., Pamela; Campos G., Alejandro (Revista Hospital Clínico Universidad de Chile, 2016)
The prevalence of diabetes has increased considerably, constituting a global epidemic today.Many of these patients will develop chronic complications of diabetes, including diabetic foot,which aggravates the patient’s clinical condition, decreases the quality of life and has a greatsocioeconomic impact. The most important action to reduce the morbidity and mortalityassociated with this pathology is the prevention of this complication, performing a propermetabolic management and serial control of the patient, educating about self-care of thefeet. Once diabetic foot ulcer is present, the cornerstones of treatment are debridement ofthe wound, management of any infection, revascularization procedures when indicated, anddischarge of the ulcer, all of the above in order to avoid amputation. This article intends tomake a review about the epidemiology, pathophysiology, classification, diagnosis, preventionand management of diabetic foot oriented to the primary care doctor